RELATIONSHIPS BETWEEN BODY MASS INDEX, EXERCISE SELF-EFFICACY AND EXERCISE CAPACITY AMONG POSTPARTUM WOMEN ATTENDING KLINIK KESIHATAN KEPALA BATAS, PULAU PINANG: A CROSSSECTIONAL STUDY - Husna Nasir; Azliyana Azizan; Syahrul Bariah Abdul Hamid (Journal of Islamic, Social, Economics and Development, 2021)
Low exercise self-efficacy has been identified as the significant predictor ofpostpartum women's problem to begin or reengage in continuous exercises routine.Simultaneously, abnormal body mass index (BMI) and low exercise capacity might besignificant in the health-related components. However, research is scarce concerning thisrelationship in postpartum women. Therefore, this cross-sectional study aimed to determine thecorrelation between BMI, exercise self-efficacy and exercise capacity among 6 to 12 months ofpostpartum women. A total of 131 postpartum women (mean = 32 ± 5 years) at Kepala BatasHealth Clinic, Pulau Pinang, were recruited. Data on demographics, BMI and exercise selfefficacyusing Malay version of Bandura Self-Efficacy Scale (ESE-M) were collected. Exercisecapacity data were measured using a 2-Minutes Step Test (TMST). About 28.3%, 13.7 %, and2.3% of the subjects were overweight, obese, and severely obese, respectively, with a mean BMIwas 24.7 ± 4.9 kg/m². About 18.3% of postpartum women had mild to moderate exercise selfefficacyand low exercise capacity (15%). There was positive correlation between BMI andexercise capacity (r=0.22, p<0.05). Meanwhile, analysis of Spearman's correlation showed apositive correlation between ESE-M behavior 1 "when I am feeling tired" and exercise capacity(r = 0.199, p <0.05). Postpartum women presented with a high level of exercise capacity mayhave an ideal BMI score and higher exercise self-efficacy. Therefore, these factors should be emphasized when healthcare professionals design interventions in promoting physical activityto encourage better physical well-being and the confidence to reengage in exercise amongpostpartum women.